Naming disorder in Alzheimer's disease patients - Οκαλίδου, Αρετή; Τσολάκη, Μάγδα; Σαραφίδου, Γιασεμί; Καζής, Αριστείδης (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF